EU-Osterweiterung: eine Bilanz nach zehn Jahren - Berthold Busch; Michael Grömling; Doris Ritzberger-Grünwald; Ognian N. Hishow; Jens Hölscher; Stefan Kolev; Joachim Zweynert (Wirtschaftsdienst, 2014)
Am 1.5.2004 sind zehn neue Mitgliedstaaten, vor allem Transformationsländer, in die EU aufgenommen worden. Drei Jahre später, am 1.1.2007, kamen Bulgarien und Rumänien hinzu. Während deutsche Unternehmer zunächst die zusätzliche Konkurrenz fürchteten, bewerten sie die Auswirkungen der Osterweiterung inzwischen positiv. Die neuen Mitgliedstaaten haben von ihrem Beitritt grundsätzlich profitiert, sogar in Hinblick auf die Beihilferegelungen konnten sie den strengen Anforderungen der EU entsprechen. Allerdings haben sich flexible Wechselkurse in der Krise für die Länder außerhalb des Euroraums als Vorteil erwiesen. Zudem leiden Rumänien und Bulgarien unter der Instabilität ihrer politischen Systeme. – – Ten years after the biggest enlargement in the history of the EU, the integration of the new member states is assessed positively. It is considered an economic success when looking at the income levels. However, due to overly optimistic assumptions and the crisis, economic integration and the catching-up process will take much longer for the new EU member states than originally expected. Moreover, new challenges are looming, especially as the Central and Eastern European accession countries adopt the euro. Smaller countries introduced the euro as quickly as possible, whereas larger countries have been much more hesitant, thinking twice not only because of several unsolved problems in the euro area but also because they use the exchange rate tool much more intensively. All new member states have to make sure they continue to increase their productivity and competitiveness. Findings suggest that after having entered the EU, the new eastern member states appear to have been developing rather stringent competition cultures. Bulgaria and Romania's transition performance signifi cantly differs from the pattern in the 2004 accession countries, both in terms of quantitative growth and institutional quality. These countries show that EU funds can be highly counter-productive since they help to conserve old structures.
Keywords: F15; O52; P20; 330; EU-Mitgliedschaft; Makroökonomischer Einfluss; Wirtschaftliche Anpassung; Entwicklungskonvergenz; EU-Staaten